1987
DOI: 10.1111/j.1432-1033.1987.tb13316.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved purification of pyruvate decarboxylase from wheat germ

Abstract: An improved procedure was developed for the isolation of pyruvate decarboxylase from wheat germ. Its final step, an electrophoresis of the native apoenzyme in concave pore gradient polyacrylamide gels, followed by superficial activity-staining, produced two bands of different molecular masses and chain compositions. The highmolecular-mass band occurred in low quantity and consisted of, probably eight, apparently identical chains of M , = 33 000, as judged from sodium dodecyl sulfate electrophoreses. The low-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 46 publications
(15 reference statements)
2
21
0
Order By: Relevance
“…The high-affinity K m value of 2n8 mM obtained for the S. ventriculi PDC is similar to the K m values obtained with many fungal and plant PDCs, including those purified from Saccharomyces cerevisiae (1-3 mM) (Boiteux & Hess, 1970 ;Hu$ bner et al, 1978), Zygosaccharomyces bisporus (1n73 mM) (Neuser et al, 2000), orange (0n8-3n2 mM) (Raymond et al, 1979), and wheat germ (3 mM) (Zehender et al, 1987). However, these K m values are several-fold higher than those reported for the PDCs of Z. mobilis (0n3-0n4 mM) (Bringer-Meyer et al, 1986 ;Neale et al, 1987b) and rice (0n25 mM) (Rivoal et al, 1990).…”
Section: Production Of S Ventriculi Pdc Proteinsupporting
confidence: 78%
“…The high-affinity K m value of 2n8 mM obtained for the S. ventriculi PDC is similar to the K m values obtained with many fungal and plant PDCs, including those purified from Saccharomyces cerevisiae (1-3 mM) (Boiteux & Hess, 1970 ;Hu$ bner et al, 1978), Zygosaccharomyces bisporus (1n73 mM) (Neuser et al, 2000), orange (0n8-3n2 mM) (Raymond et al, 1979), and wheat germ (3 mM) (Zehender et al, 1987). However, these K m values are several-fold higher than those reported for the PDCs of Z. mobilis (0n3-0n4 mM) (Bringer-Meyer et al, 1986 ;Neale et al, 1987b) and rice (0n25 mM) (Rivoal et al, 1990).…”
Section: Production Of S Ventriculi Pdc Proteinsupporting
confidence: 78%
“…The decarboxylation reaction of POR must therefore differ from that of pyruvate decarboxylases. Pyruvate decarboxylases have been purified from a variety of organisms (37)(38)(39)(40)(41) and the crystal structure of one is known (42,43). That they are also TPP-containing enzymes and the mechanism of pyruvate decarboxylation, which does involve direct conversion of the hydroxyethyl-TPP complex to the aldehyde, is well understood (43)(44)(45).…”
Section: Resultsmentioning
confidence: 99%
“…They also found that the M r 44 000 polypeptide increased in amount during storage. Zehender et al [34] found a major form of wheat germ PDC to have two type of chains: alpha of 63 000-65 000, and beta of61000-62000. Laszlo [20] provided data suggesting that the smaller subunit was derived from the larger subunit by proteolytic cleavage.…”
Section: Discussionmentioning
confidence: 99%